Ambulatory surgery in proctology: retrospective analysis of 1 031 cases - Hossne, Rogério Saad [UNESP]; Bakonyi Neto, Alexandre [UNESP]; Gamberini Prado, Rene (Soc Iberoamericana Informacion Cientifica-s I I C, 2008)
Introduction: The number of ambulatory surgeries accomplished in hospitals, as in private clinics, grows each day, with this increase having been observed principally in the last two decades. In many countries, such as France, ambulatory surgeries have predominated in relation to those in hospitals. Objective: To evaluate retrospectively 1 031 cases of patients operated on in the Ambulatory Surgery Service of CH. in the School of Medicine at Botucatu. Material and method: Retrospectively, 1 031 clinical cases of orificial pathologies operated on in the service were studied, analyzing the distribution by age group, sex, pathologies and postoperative complications. Result: We note predominance of patients aged less than 45 years (56.6%), discrete prevalence of males (51.2%), with hemorrhoidal disease (60%) being the principal affliction, with pain and bleeding being the most frequent complications (3.2%). Conclusions: The results obtained demonstrate that ambulatory procedures in proctology can be accomplished in a safe and systematic manner at low cost with advantages and fewer complications in relation to procedures completed in a hospitalization regime.
Keywords: surgery; ambulatory; proctology